Graphene-Coupled Flower-Like Ni3S2 for a Free-Standing 3D Aerogel with an Ultra-High Electrochemical Capacity. (10th February 2016) - Lin, Hualin; Liu, Fan; Wang, Xinjing; Ai, Yani; Yao, Zhaoquan; Chu, Lei; Han, Sheng; Zhuang, Xiaodong
Abstract: Graphene-coupled flower-like nickel sulfide monoliths that exhibit ultra-light, mesoporous structures and uniform particle sizes are successfully prepared using an F127-assisted hydrothermal method and high-temperature pyrolysis. As an electrode material for supercapacitors, the as-prepared rGO-Ni3 S2 shows ultra-high specific capacitances of 1315 and 1050 F g −1 at 1 and 10 A g −1, respectively. After 1000 charge/discharge cycles at a current density of 1 A g −1, the specific capacitance increases by almost 15%, indicating the excellent capacitance and durability of rGO-Ni3 S2 . Further, an asymmetric supercapacitor using rGO-Ni3 S2 as positive electrode and active carbon as negative electrode exhibits high specific capacitance of 104.6 F g −1 at 0.5 A g −1, and excellent cycling stability with 85.6% capacitance retention after 5000 cycles at a current density of 4 A g −1 . These promising supercapacitor performances demonstrate that the as-developed surfactant-assisted hydrothermal strategy can be widely used to prepare graphene-coupled metal sulfides for high-performance supercapacitor applications.